Open Unemployment Rate in The Province of East Java - Andaru Rachmaning Dias Prayitno; Deni Kusumawardani (The Winners, 2022)
Economic development is basically a series of policy efforts that have the aim of increasing the standard of living of the people, directing income distribution, and expanding employment opportunities. In efforts to develop the economy, employment is still a major issue. This is due to inequality in getting job opportunities. The growth in the number of the workforce with progress in various economic sectors is not balanced. The research aimed to study the effect of gross regional domestic product (GRDP), provincial minimum wage (PMW), and inflation on the open unemployment rate in East Java province. The research used secondary data for the period 2006 - 2017 which consists of the value of GRDP, East Java PMW, East Java province inflation, and East Java province open unemployment rate. By applying regression using panel data regression analysis, the research results show that GRDP and Inflation has a negative and significant effect on the open unemployment rate in East Java. The PMW has a positive and significant effect on the open unemployment rate in East Java Province. Nevertheless, the research highlights effect relation and government policy instruments.